Load balancing mechanism for clustered PMIPv6 protocol - Ghaleb, Safwan M.; Subramaniam, Shamala; Ahmad Zukarnain, Zuriati; Muhammed, Abdullah (SpringerOpen, 2018)
Proxy Mobile IPv6 (PMIPv6) has become a credible member of pertinent research areas. This is attributed mainly to its capability of enabling mobility without imposing constraints or requirements on the mobile node (MN). This MN shield is enabled due to the transferring of mobility-related signaling to a new entity, which is called Mobile Access Gateway (MAG). However, associating MNs to a specific MAG inside the PMIPv6 network increases the MAG load probability. Thus, several research have enhanced the PMIPv6 protocol to improve its basic specifications and performance. Strategies include protocols, which apply the clustering technique to enhance the overall performance of the PMIPv6 in terms of routing, scalability, lifetime, and load balancing. The load balancing mechanism is considered in the non-clustered protocols. However, this mechanism has not been adopted in clustering-based protocols. Thus, pertaining to the load and the respective assignments is critical. In this article, to address these issues, a new load balancing mechanism is proposed among MAGs for Cluster-based Proxy Mobile IPv6 (CSPMIPv6) protocol. The signaling within the CSPMIPv6 has been enhanced to support the proposed load balancing mechanism. The proposed mechanism employs the inter- and intra-domain on a frequent basis to select the best MAG among the candidate MAGs. The new mechanism has improved the performance to create an evident improvement in terms of average queuing delay, handover latencies, transmission rate, end-to-end delay, and packet loss as compared to the LBM-PMIPv6 mechanism and CSPMIPv6 protocol.